A comparative study of chromatographic lipophilicity and bioactivity parameters of selected spirohydantoins. Issue 19 (13th December 2020) - Tot, Kristina; Lazić, Anita; Djaković Sekulić, Tatjana
Abstract: In this study, lipophilicity of 21 cycloalkylspiro-5-hidantoins was assessed. The overall goal of lipophilicity evaluation is preliminary investigation which should result in a decrease of the traditionally high attrition rates for compounds entering clinical trials. Lipophilicity assessment was done by reversed-phase thin-layer chromatography and in silico methods. Chromatographic analyses were performed on C-18 modified thin-layer of silica gel with a two-component mobile phase consisting of water and organic solvent (acetonitrile, acetone, dioxane, or tetrahydrofuran) in different ratios. The chromatographic lipophilicities ( R M 0 ) were discussed and compared with computational log P s calculated with various algorithms as well as in silico ADMET descriptors using linear regression and multivariate approach (hierarchical cluster analysis and principal component analysis). A high correlation was obtained between R M 0 values and calculated log P indicating a strong relationship between the variables. Multivariate data analysis enabled the comparison of the chemical structures, lipophilicity, pharmacokinetic predictors and toxicity of the investigated compounds. Graphical Abstract: